A micromechanics-based framework to predict transitions between dimple and cup-cone fracture modes in shocked metallic glasses. (February 2021) - Tang, X.C.; Yao, X.H.; Wilkerson, Justin W.
Abstract: In an earlier work (Tang et al., 2020), we derived evolution equations governing dynamic void growth in amorphous materials with a number of idealizing assumptions. Here, we extend and further generalize the constitutive theory to better account for general stress states, strain-softening, stable and unstable void growth modes, as well as viscous and micro-inertial retarding effects on void growth rates. The enhanced theory is implemented into a commercial finite element software package via a user-defined material subroutine to understand transitions in fracture morphologies. In particular, metallic glasses exhibit a dimple type fracture mode at low impact velocities, which transitions to a cup-cone type fracture mode at higher impact velocities. Our theory reveals that two competing processes drive this transition: (i) strain-softening behavior that is inherent to many amorphous materials and (ii) a so-called stress plateau effect that arises due to bursts of stable and unstable void growth. Our simulation results also suggest that strain-softening during the dynamic compression phase, which precedes subsequent tensile failure, is essential to the formation of cup-cone fracture morphology. Highlights: Full micromechanics-based constitutive framework for metallic glasses. Elucidation of fundamental mechanisms governing fracture morphology. Strong coupling of amorphous plasticity and damage nucleation is exhibited. Strain-softening behavior is essential to the formation of cup-cone fracture.